Controlled type II diabetes mellitus has no major influence on platelet micro-RNA expression - Stratz, Christian; Nührenberg, Thomas; Fiebich, Bernd L.; Amann, Michael; Kumar, Asit; Binder, Harald; Hoffmann, Isabell; Valina, Christian; Hochholzer, Willibald; Trenk, Dietmar; Neumann, Franz-Josef (Thrombosis and Haemostasis, 2014)
Diabetes mellitus as a major contributor to cardiovascular disease burden induces dysfunctional platelets. Platelets contain abundant miRNAs, which are linked to inflammatory responses and, thus, may play a role in atherogenesis. While diabetes mellitus affects plasma miRNAs, no data exist on platelet miRNA profiles in this disease. Therefore, this study sought to explore the miRNA profile of platelets in patients with diabetes mellitus that is unrelated to the presence or absence of coronary artery disease (CAD). Platelet miRNA profiles were assessed in stable diabetic and non-diabetic patients (each n=30); 15 patients in each group had CAD. Platelet miRNA was isolated from leucocyte-depleted platelet-rich plasma, and miRNA profiling was performed using LNA micro-array technology (miRBase18.0, containing 1,917 human miRNAs). Effects of diabetes mellitus were explored by univariate statistical tests for each miRNA, adjusted for potential confounders, and by developing a multivariable signature; evaluated by resampling techniques. Platelets in non-diabetic patients demonstrated miRNA expression profiles comparable to previous data. The miRNA profiles of platelets in diabetics were similar. Statistical analysis unveiled three miRNAs (miR-377–5p, miR-628–3p, miR-3137) with high reselection probabilities in resampling techniques, corresponding to signatures with modest discriminatory performance. Functional annotation of predicted targets for these miRNAs pointed towards an influence of diabetes mellitus on mRNA processing. We did not find major differences in platelet miRNA profiles between diabetics and non-diabetics. Minor differences pertained to miRNAs associated with mRNA processing. Thus, described differences in plasma miRNAs between diabetic and non-diabetic patients cannot be explained by plain changes in platelet miRNA profile.
Keywords: Platelets; miRNA; type 2 diabetes mellitus; microarray